P-187 A revolution in the care of heart failure patients. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Marvin, Ros; Bell, Sarah; Pheasant, May
Abstract : Background: Nearly a million people in the UK live with heart failure (HF) (Hospice UK, 2017). 30–40% of patients die within a year of diagnosis, yet despite a high symptom burden they make up only around 4% of those receiving specialist palliative care services (Hospice UK, 2017). Two hospices working collaboratively received a grant from Hospice UK to bridge the gap between their care and the local NHS hospital trust cardiology team. Aims: To improve care for heart failure patients by: Providing a joined–up service for HF patients Developing a regional HF referral pathway Increasing hospice referrals Upskilling and educating the cardiology, specialist palliative care (SPC) and community healthcare teams Providing fatigue and breathlessness (FAB) courses. Actions: A consultant from one hospice and CNSs from the other hospice attended weekly hospital HF clinics and monthly multidisciplinary team meetings. Hospices ran off-site, HF specific FAB courses. A regional referral pathway between cardiology and SPC was developed. Hospices held educational events for GPs and community healthcare professionals on HF management and palliation. Outcomes: Development of strong links between cardiology and SPC, increasing collaboration and knowledge within SPC and cardiology teams about the others roles. HF referrals to the hospices doubled, with twice the national average of HF patients receiving hospice care. Patients accessed increased palliative support, holistic symptom management, advance care planning and family support. Patient reported improvements in breathlessness, fatigue, weakness and quality of life following HF FAB courses. Excellent feedback following community healthcare professionals' HF management and palliation education events. Conclusion: This collaborative project revolutionised the ongoing ability of cardiology and SPC to jointly manage HF patients' palliative care needs, resulting in a doubling in hospice referrals for HF patients. SPC support, including hospice referral and FAB courses, reduced HF patients' reported symptom burden. Community professionals' knowledge of the importance of SPC for HF patients was increased, supported by a comprehensive new referral pathway.